The role of lycopene in alleviating soybean meal-induced intestinal injury in an early-weaned piglet model - Zheng, Shugui; Li, Mingbo; Luan, Xinhong; Tong, Chuan; Li, Jiguang; Zhang, Zhiying (Frontiers in Veterinary Science, 2025)
IntroductionSoybean meal (SBM), widely used in pig farming, can induce intestinal damage and dysfunction in newly-weaned piglets due to the presence of soybean antigen proteins. However, research on natural compounds capable of mitigating these adverse effects remains limited. This study investigated the effects of lycopene, a carotenoid, on the intestinal health of piglets fed a SBM-based diet.MethodsEighteen 21-day-old piglets were randomly assigned to three treatment groups: a negative control (NC) group fed an animal protein-based diet, a positive control (PC) group fed a SBM-based diet, and a lycopene group, which received the PC diet supplemented with lycopene. Growth performance, antioxidant capacity, cell apoptosis, intestinal barrier function, intestinal histomorphology, and gut microbiota composition of piglets in each group were systematically evaluated.ResultsDietary lycopene significantly improved average daily gain (ADG) and average daily feed intake (ADFI) while reducing incidence of diarrhea in early-weaned piglets. Lycopene enhanced antioxidant capacity, as evidenced by increased superoxide dismutase (SOD) activity and total antioxidant capacity (T-AOC) in body. Additionally, lycopene reduced apoptosis in small intestinal cells and strengthened intestinal barrier function, as indicated by decreased serum diamine oxidase (DAO) levels. It also improved small intestinal histomorphology, characterized by increased villus height and reduced crypt depth. Furthermore, lycopene modulated gut microbiota by promoting the growth of beneficial bacteria, particularly Lactobacillus, while reducing the abundance of harmful bacteria.ConclusionThese findings demonstrated that lycopene supplementation in SBM-based diets significantly enhanced antioxidant capacity, decreased apoptosis in small intestinal cells, improved intestinal barrier function and morphology, and optimized gut microbiota composition. These beneficial effects collectively contributed to improved intestinal health and enhanced production performance in piglets fed a SBM-based diet.